Sacubitril/Valsartan Improves Cardiac Function and Decreases Myocardial Fibrosis Via Downregulation of Exosomal miR‐181a in a Rodent Chronic Myocardial Infarction Model. Issue 13 (7th July 2020) - Vaskova, Evgeniya; Ikeda, Gentaro; Tada, Yuko; Wahlquist, Christine; Mercola, Marc; Yang, Phillip C.
Abstract : Background: Exosomes are small extracellular vesicles that function as intercellular messengers and effectors. Exosomal cargo contains regulatory small molecules, including miRNAs, mRNAs, lncRNAs, and small peptides that can be modulated by different pathological stimuli to the cells. One of the main mechanisms of action of drug therapy may be the altered production and/or content of the exosomes. Methods and Results: We studied the effects on exosome production and content by neprilysin inhibitor/angiotensin receptor blockers, sacubitril/valsartan and valsartan alone, using human‐induced pluripotent stem cell‐derived cardiomyocytes under normoxic and hypoxic injury model in vitro, and assessed for physiologic correlation using an ischemic myocardial injury rodent model in vivo. We demonstrated that the treatment with sacubitril/valsartan and valsartan alone resulted in the increased production of exosomes by induced pluripotent stem cell‐derived cardiomyocytes in vitro in both conditions as well as in the rat plasma in vivo. Next‐generation sequencing of these exosomes exhibited downregulation of the expression of rno‐miR‐181a in the sacubitril/valsartan treatment group. In vivo studies employing chronic rodent myocardial injury model demonstrated that miR‐181a antagomir has a beneficial effect on cardiac function. Subsequently, immunohistochemical and molecular studies suggested that the downregulation of miR‐181a resulted in the attenuation of myocardial fibrosis and hypertrophy, restoring the injured rodent heart after myocardial infarction. Conclusions: We demonstrate that an additional mechanism of action of the pleiotropic effects of sacubitril/valsartan may be mediated by the modulation of the miRNA expression level in the exosome payload.